2019
DOI: 10.3991/ijim.v13i07.10845
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Learning Through Mobile Apps: A Phenomenological Inquiry of Student Acceptance and Desired Apps Features

Abstract: Vocabulary plays a great role in language learning as learners would face difficulties in language learning if they have insufficient vocabulary knowledge. The advent of new technologies has encouraged the development of mobile assisted language learning (MALL) and the increase in mobile apps for vocabulary learning. Nonetheless, it would seem that there is a dearth in research on the use of mobile apps for vocabulary learning especially in our local contexts. Capitalising on the strength of phenomenological i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 7 publications
10
49
0
1
Order By: Relevance
“…Firstly, it is clear that students appreciated the accessibility of the mobile app anywhere and at any time more than the traditional books, provided there was Internet access. This is in line with the findings of a Malaysian study [14] whose authors surveyed 33 students on the acceptance of mobile app for language learning. They found that it was easy for the students to download the app, which is easy to carry everywhere and accessible at their preferred time and place.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Firstly, it is clear that students appreciated the accessibility of the mobile app anywhere and at any time more than the traditional books, provided there was Internet access. This is in line with the findings of a Malaysian study [14] whose authors surveyed 33 students on the acceptance of mobile app for language learning. They found that it was easy for the students to download the app, which is easy to carry everywhere and accessible at their preferred time and place.…”
Section: Resultssupporting
confidence: 88%
“…This is in line with a research study by Kwangsawad [13] and Elaish et al [19], who reported that their students also had found using smartphones in EFL classes more fun, beneficial and productive. Similar findings were provided by Deris and Shukor [14]. As Ozer and Kilic [16] maintain, the more students use the mobile devices, the more academic gains they are able to achieve.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…A number of studies evaluated the use of mobile learning for usability. For instance, researchers [23] concluded a positive acceptance of the use of mobile application in learning vocabulary by the students based on the good scores given to aspects such as ease of use and usefulness. An experimental study in elementary schools was presented in [24].…”
mentioning
confidence: 99%